Trotter – Daletskii formula for nonlinear disturbance - Bondarenko, V. G. (Ukrains’kyi Matematychnyi Zhurnal, 2018)
For a semilinear parabolic equation, we prove a relation generalizing the Trotter – Daletskii formula.